2017
DOI: 10.1371/journal.pone.0175408
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective observational evaluation of postoperative oxygen saturation levels and associated postoperative respiratory complications and hospital resource utilization

Abstract: IntroductionThe clinical importance of postoperative episodic hypoxemia is still unclear, and therefore largely under-studied. As a result, there is limited understanding of its relationship with early postoperative respiratory complications (PRC, defined as intubation within three days of surgery) and hospital resource utilization.Materials and methodsThis single center study was performed using a retrospective observational design. We described population based definitions of desaturation from continuous SpO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 48 publications
7
18
0
Order By: Relevance
“…28 Moreover, even if post-operative hypoxemia does not lead to respiratory arrest, it is known to be associated with various post-operative adverse outcomes. 29,30 We found that among the alarm signs, hypoxemia in patients admitted to the ward after non-cardiac surgery was more often associated with increased post-operative in-hospital mortality, which is consistent with the results of previous studies. 29,30 The findings in our study suggest that total CO 2 and post-operative hypoxemia should be monitored more carefully than other alarm signs.…”
Section: Discussionsupporting
confidence: 91%
“…28 Moreover, even if post-operative hypoxemia does not lead to respiratory arrest, it is known to be associated with various post-operative adverse outcomes. 29,30 We found that among the alarm signs, hypoxemia in patients admitted to the ward after non-cardiac surgery was more often associated with increased post-operative in-hospital mortality, which is consistent with the results of previous studies. 29,30 The findings in our study suggest that total CO 2 and post-operative hypoxemia should be monitored more carefully than other alarm signs.…”
Section: Discussionsupporting
confidence: 91%
“…We found that patients who experienced early postoperative desaturation were at higher risk of complications and loss of functional independence that may be explained by a hypoxaemia‐induced decrease in oxygen delivery. Peri‐operative hypoxaemia increases the odds of acute MI , AKI and respiratory complications , all of which we found in our study population after just a brief episode of postoperative desaturation. Hypoxaemia is also known to lead to systematic vasodilation and to have meaningful effects on cellular metabolism, central nervous system and several other organ systems .…”
Section: Discussionsupporting
confidence: 61%
“…It has also been demonstrated that the duration of O 2 therapy was an independent risk factor for developing postoperative respiratory complications. Patients who require O 2 for ≥75% of recovery room time (or greater than 90 min) appear to be at greater risk of developing respiratory complications 45. This fact may suggest that some patients are not adequately screened for risk factors such as OSA by standard preanaesthesia testing, and that a device dedicated to continuous monitoring of O 2 administration (either alarms on duration and flow variations) may help to detect such high-risk patients.…”
Section: Discussionmentioning
confidence: 99%